A double-blind, placebo-controlled, phase II, randomized study of lovastatin therapy in the treatment of mildly active rheumatoid arthritis. (18th October 2019) - Aranow, Cynthia; Cush, John; Bolster, Marcy B; Striebich, Christopher C; Dall'era, Maria; Mackay, Meggan; Olech, Ewa; Frech, Tracy; Box, Jane; Keating, Richard; Wasko, Mary Chester; St Clair, William; et al.
Abstract: Objectives: 3-hydroxy-3-methylglutaryl coenzyme-A (HMG Co-A) reductase inhibitors (statins) are standard treatment for hyperlipidaemia. In addition to lipid-lowering abilities, statins exhibit multiple anti-inflammatory effects. The objectives of this study were to determine whether treatment of patients with RA with lovastatin decreased CRP or reduced disease activity. Methods: We conducted a randomized double-blind placebo-controlled 12 week trial of lovastatin vs placebo in 64 RA patients with mild clinical disease activity but an elevated CRP. The primary efficacy end point was the reduction in mean log CRP. Secondary end points included disease activity, RF and anti–CCP antibody titres. Mechanistic end points included levels of serum cytokines. Safety was assessed; hepatic and muscle toxicities were of particular interest. Results: Baseline features were similar between groups. No significant difference in mean log CRP reduction between the two groups was observed, and disease activity did not change from baseline in either treatment group. Mechanistic analyses did not reveal significant changes in any biomarkers. A post hoc analysis of subjects not using biologic therapy demonstrated a significantly greater proportion achieving ⩾20% reduction in CRP from baseline in the lovastatin group compared with placebo ( P -value = 0.007). No difference was observed in subjects receiving biologics. Lovastatin was well tolerated with no serious safety concerns. Conclusion: This study showed no anti-inflammatory or clinical effects on RA disease activity after 12 weeks of treatment with lovastatin. Lovastatin had a modest effect on CRP in subjects not using biologics, suggesting statins may be anti-inflammatory in selected patients. Trial registration: ClinicalTrials.gov, http://clinicaltrials.gov, NCT00302952.